Okara Yogurt Formulation as Functional Food to Prevent Stunting - Putri, Syadila Nugraheny Muliya; Nursini, Ni Wayan; Wiradnyani, Ni Ketut (MultiTech Publisher, 2024)
Okara is the waste produced during soybean tofu production. To reduce okara waste, it is converted into functional food. Okara yogurt is formulated as a functional food to prevent stunting. The problem in this study is how the okara yogurt formulation can produce protein levels, fat levels, carbohydrate levels, water levels, ash levels, and acidity for the nutritional fulfilment of stunting, how the lactic acid bacterial population in okara yoghurt, and how organoleptic testing of okara yogurt products. This study uses RAL with 6 treatments and 3 repetitions. The data was analyzed statistically using analysis of variance (ANOVA) and continued with the tukey test. Organoleptic tests on selected formulas are Y5 color with value (3.47), Y3 texture with value (3.50), Y3 aroma with value (3.50), Y3 taste with value (3.67) and Y5 liking with value (3.67) per 100 grams. In making okara yogurt, it is recommended to use the selected formula, namely Y3